Anatomy and physiology of the sentinel lymph nodes of the upper extremity: Implications for axillary reverse mapping in breast cancer. Issue 4 (17th December 2020) - Coroneos, Christopher J.; Woodward, Wendy A.; Wong, Franklin C.; Caudle, Abigail S.; Shaitelman, Simona F.; Kuerer, Henry M.; Schaverien, Mark V.
Abstract: Background: This study characterizes the physiological drainage of the normal upper extremity using single‐photon emission computed tomography/computed tomography (SPECT/CT) lymphoscintigraphy axillary reverse lymphatic mapping (ARM). Methods: A consecutive series of patients assessed with SPECT/CT lymphoscintigraphy ARM of the upper extremity were included. Anatomical localization of the axillary sentinel lymph nodes (SLN) was completed in normal axillae in relation to consistent anatomic landmarks. Retrospective case note analysis was performed to collect patient demographic data. Results: A total of 169 patients underwent SPECT/CT lymphoscintigraphy, and imaging of 182 normal axillae was obtained. All patients (100%) had an axillary SLN identified: 19% had a single contrast‐enhanced SLN in the axilla and the remainder had multiple. The SLN(s) of the upper extremity was located in the upper outer quadrant (UOQ) of the axilla in 97% of cases (177 axillae). When the SLN(s) was found in the UOQ of the axilla, second‐tier lymph nodes were found predominantly in the upper inner quadrant (50% of cases). Conclusions: The upper extremity SLN(s) is located in a constant region of the axilla. This study provides the most complete investigation to date and results can be directly applied clinically to ARM techniques and adjuvant radiation planning.